Perancangan Proses Bisnis UMKM Toko Roti Amira Menggunakan Business Process Model and Notation - Miftah Khairunnisa Nasution; Ummi Aulia; Muhammad Dafa Lubis; Dery Shadani; Rizky Putra Halomoan Harahap; Ika Yusnita Sari (GLOBAL SCIENTS PUBLISHER, 2026)
Amira Bakery, as a Micro, Small, and Medium Enterprise (MSME), still operates without structured documentation, resulting in operational inefficiencies and difficulties in decision-making. This study aims to analyze and map Amira Bakery's business processes using Business Process Model and Notation (BPMN). The research method used is qualitative with a case study approach. The research data consists of primary data obtained through direct observation of operational activities and interviews with the owner and employees, and the data is analyzed by modeling the business processes into AS-IS and TO-BE BPMN diagrams. The results of the study show that BPMN is capable of systematically describing business process flows, identifying process obstacles, and providing recommendations for improvements to increase operational efficiency and effectiveness.